Anti-angiogenesis or pro-angiogenesis for cancer treatment: focus on drug distribution - Huang, Dongsheng (Int J Clin Exp Med, 2015)
Enhancing chemotherapy delivery to tumors, improving tumor growth control, reducing metastasis, and increasing survival are all critical objectives of improved cancer therapy. One of the obstacles to the success of anticancer therapies is related to the inefficient distribution of drugs to tumor cells. To be effective, chemotherapeutics must reach a concentration in cancer cells that is sufficient to inhibit its targets. In the past years, the vascular normalization theory has gained widespread acceptance for explaining additional antitumor effects of inhibitors of vascular endothelial growth factor (VEGF) signaling, when combined with chemotherapeutics. Vascular normalization is a strategy to enhance the antitumor effects of chemotherapeutics, but this is time and dose dependent and therefore difficult to implement clinically. Thus, alternative strategies that overcome these issues are needed. Accumulating scientific data demonstrate an alternative approach called “vascular promotion therapy” can increase chemotherapeutics delivery and intracellular uptake of the drug and reduces hypoxia by increasing tumor blood vessel density, blood flow, leakiness, and dilation, which leads to reduced cancer growth and metastasis. In this article, we first summarize the structural and functional abnormalities of the tumor microvasculature to highlight the importance of this phenomenon for chemotherapeutics distribution. Next, we summarize the limitations of anti-angiogenic strategy in cancer treatment, discuss some key prototypical underlying mechanisms of vascular normalization and initial clinical evidence of vascular promotion therapy, and speculate on the clinical potential of anticoagulation as a novel paradigm to improve cancer treatment.